Private university lecturer's professional commitment in Jakarta - Marisa Permatasari; Dedi Purwana; Maruf Akbar (Program Studi S3 Ilmu Manajemen, 2020)
This study aims to analyze the effect of transformational leadership, academic culture, self – engagement on lecturer’s professional commitment of private university in Jakarta. A quantitative approach were used in the study. Data were analyzed from 212 lecturers of B-Accreditation private universities in Jakarta using Structural Equation Modelling (SEM). The findings delivers two things; First, there were positive and significant effect of transformational leadership on lecturer’s professional commitment; self – engagement on lecturer’s professional commitment; transformational leadership on academic culture; academic culture on self – engagement. Second, there were no significant effect of academic culture on lecturer’s professional commitment; transformational leadership on self – engagement.